Availability, accessibility and acceptance (3As) of advanced digital technologies among higher education students with special needs in Oyo State, Nigeria (2018)
The world has become a global village. It is now crystal clear that life at present is different from life few decades ago. Nowadays, every society is striving for apt knowledge that can he used as panacea to solve their myriad problems. Previous studies have focused largely on the use of digital technologies among students without special needs with little consideration to students with special needs. Therefore, this paper investigated the availability, accessibility and acceptance of advanced digital technologies among higher education students with special needs in Oyo State, Nigeria. The descriptive research method was employed while the multi stage sampling procedure was used to select the sample for the study. First, purposive e sampling technique was used to select two higher education institutions that are owned by the federal government of Nigeria (one college of education and one university). Second, random sampling technique of the ballot method was used to select one hundred and forty (140) participants with special needs (those with hearing impairment were 125 and those with visual impairment were 15). Two structured questionnaires on availability, acceptance and accessibility of advanced digital technologies by higher education students with special needs were used for data collection. To guide the study, six research questions were raised and tested at 0.05 level of significance. The data was collated and analysed using the descriptive statistics of percentages, means and standard deviation. li was found that for higher education students with hearing impairment, digital technologies are poorly available and inaccessible. However, among higher education students with visual impairment, there is moderate availability, accessibility and acceptance of digital technologies. Based on the findings, it was recommended that the Nigerian government at all levels should brace up to their responsibilities and provide digital technologies for students with special needs particularly, those with hearing impairment in higher educational institutions in the country.